Inheritance of anthracnose resistance in common bean accession G 2333 - Pastor Corrales, Marcial A.; Erazo, OA; Estrada Salazar, EI (Scientific Societies, 1994)
Common bean (Phaseolus vulgaris) germ plasm accession G 2333 (Colorado de Teopisca) from Mexico was resistant to 380 isolates of the anthracnose pathogen (Colletotrichum lindemuthianum) from 11 Latin American countries. Six frequently used sources of resistance were susceptiblc to many isolates. Inheritance of resistance was studied in a cross of resistant G 2333 x susceptible ICA Pijao. The two parents and the F1, F2, and backcross generations were inoculated with race 521 in both the seedling and adult-plant stages in controlled greenhouse environments at CIAT. Two independent dominant genes controlled resistance in the seedling and adult-plant stages, giving a segregation ratio of 15 resistant to 1 susceptible in the F2, all resistant in the backcross to G 2333, and 3 resistant to I susceptible in the backcross to ICA Pijao.